Investigating factors contributing to effective learning in in-service teacher training in student individual health domain: A qualitative study - hamed eskandari; amanollah soltani; Vida Andishmand; Amir Soltani (Kerman University of Medical Sciences, 2020)
Introduction: What is important in educational courses is transferring the acquired information and knowledge to the workplace. This study aimed to determine factors contributing to effective learning in teachers' in-service training programs in the student individual health domain. Methods: This study was conducted in 2018 using a qualitative approach and the content analysis method. The data were collected through semi-structured interviews. The participants in this study were 23 teachers who were selected using a purposive sampling method among teachers working in Kerman. The main question asked in the interviews was factors contributing to effective learning teacher's in-service training programs in the student individual health domain. A qualitative content analysis method was used to analyze the data. The validity of the research findings was guaranteed by peer reviews and multi-stratified data sources. Results: The factors underlying effective learning in student individual health domain were placed into three categories; individual factors include Self-efficiency, Motivation to learn health-related concepts, individual capacity to learn health-related concepts, and Attitude toward health-related concepts. Organizationa Factors, include Learning environment and educational factors include Educational strategies for the health-related concepts. Conclusion: Regardless of the attitudes, motivation, and efficiency of the participants, paying attention to their readiness to learn, providing necessary support, providing facilities and equipment, and paying attention to the needs of teachers are the most important factors that facilitate application of lessons learned in the workplace.